Nueva ciudadanía para el tercer milenio - Gloria Pérez Serrano (Universidad de La Rioja, 2013)
The concept of citizenship in multicultural societies is undergoing a series of deep changes. This new citizenship which is emerging in the dawn of the Third Millenium presents different requirements and possibilities and citizens must be ready to face them. In this work, we consider the horizons of the new citizenship, the links between citizenship and nationality, the development of proper critical citizens, as well as the dimensions of this citizenship, namely democratic, social, equal, intercultural and environmental. The fact that citizens in current societies must be able to build their identity on the basis of multiple memberships and learn to coexist in diversity is also highlighted.